Red Ginger as an Immunomodulator - Safitri, Ayu; Salsabilla, Shofa Tsuraya; Marselino, Doni I. P.; Noraisyah, Dila; Karina, Diah (Universitas Ibn Khaldun Bogor, 2024)
This study aims to examine the potential of red ginger (Zingiber officinale var. rubrum) as an immunomodulator based on various literature sources from books and journals. Red ginger, which is known to have a high bioactive content, has been used in traditional medicine to boost immunity. This study examined the chemical composition, mechanism of action, and scientific evidence that supports the effectiveness of red ginger as an immunomodulator. The results of the study show that red ginger has great potential to be developed as an effective and safe immunomodulator product.